The Effect of Environmental Disclosure Practices on Firm Value of Malaysian Listed Firms - Mohd Waliuddin, Mohd Razali; Mohd Firdaus, Zakaria; Siti Nur Sahira, Musa; Damien Lee, Lung Yau; Nurul Izza, Abd Malek; Mohamad Ikhram, Mohamad Ridzuan (UKR Publisher, 2025)
There are no clear laws in Malaysia requiring firms to disclose environmental information, although the Department of Environment and the Occupational Safety and Health Act mandate some disclosures, which creates uncertainty for investors and complicates the assessment of environmental risks and liabilities associated with their investments. In Agency theory, environmental disclosure reduces information gaps, which in turn increases the value of a firm, thereby aligning the interests of investors and managers. According to Legitimacy Theory, firms disclose environmental information to satisfy societal expectationsand secure public approval, increasing their market value. This paper tries to find the relationship between environmental disclosure and firm value within a final sample of 344 firms listed in Bursa Malaysia. The non-financial data, which are environmental disclosure and firm age, were collected in the annual report, while other remaining data, such as firm size, leverage, profitability, and turnover ratio, were collected from Orbis's database. The panel regression analysis shows that environmental disclosure has a positive relationship with firm value. Investors and firms should acknowledge the enduring advantages of openness in environmental practices, as it enhances market valuation and aligns with the increasing desire for sustainable company operations.